UPAYA MEMPERTAHANKAN HAK KONSUMEN MELALUI PENYELESAIAN SENGKETA DENGAN CARA KONSILIASI DI BADAN PENYELESAIAN SENGKETA KONSUMEN KOTA MEDAN - Sirait, Cindy Octabriel; Sidabalok, Janus; Suhardin, Yohanes (Universitas Katolik Santo Thomas Medan, 2022)
The purpose of this study was to determine the process of resolving consumer disputes by means of conciliation and to determine the efforts to defend consumer rights at the Medan Consumer Dispute Settlement Agency (BPSK).This research is descriptive, using normative-empirical research methods with a focus on the enforcement or implementation of normative legal provisions on consumer dispute resolution. Data or information obtained from BPSK Medan. in the form of notes and information regarding the settlement of consumer disputes by means of conciliation. The results show that the consumer dispute resolution process at BPSK Medan City is different from that regulated in Law No. 8/1989 on Consumer Protection and Decree of the Minister of Industry and Trade No.350/MPP/Kep/12/2001 concerning Implementation of Duties and Authorities BPSK. Disputes are resolved by the parties accompanied by a conciliator assembly appointed by the BPSK leadership. After the parties obtain an agreement, then it is reported to BPSK which is then stated in a peace agreement which will be strengthened by the BPSK Decision. In fact, consumer disputes were resolved by parties outside of BPSK after BPSK held the first meeting, and subsequently the final settlement was not reported so that BPSK could not make decisions to strengthen the peace reached by the parties.